Religion and politics in South Africa: from apartheid to democracy - Tayob, Abdulkader; Weiße, Wolfram (Religion and society in transition, 2000)
Klappentext: From the mid-1970s, the awareness of injustice and apartheid in South Africa increased in the media and in scholarship. From the secular perspective, it was no surprise to find a Christian denomination directly involved in the formulation of the apartheid-doctrine. However, it was far more surprising to fing opposition leaders, even many members of the African National Congress, referring in their strucggle to religious doctrines. South Africa imposed a challenge to all the voices that claimed that the process of democratisation was only possible through secularisation. The contributions to this book represent a spectrum of religious and political perspectives in South Africa in their social context. Some tackle the important question of transformation within religions. Since the period of transition and democracy, the country is witness to a re-ordering and re-classification of values and priorities within society and religious traditions. The contributions also focus on the possible role of religions in fashioning values and identities on a broad national scale. They subject to evaluation multi-culturalism, education, and development under the impact of religious values, ethics and symbols.